Liberalization of the capital account: experiences and issues - Mathieson, Donald J. (IMF WashingtonUS, 1993)
Reviews the experiences of industrial and developing countries with capital controls and considers some of the key policy issues raised by the diminished effectiveness of capital countries. Examines the potential medium-term benefits and costs of an open capital account, and analyzes the policy measures that could help sustain capital account convertibility.